Lateral networks of teachers in a centralised education system: Structures, processes, and development of teacher agency. Issue 4 (1st October 2020) - Shaari, Imran
ABSTRACT: There are proliferations of lateral networks in the education system. This study investigates the functioning of lateral networks of teachers in a centralized system, focusing on the enabling structures and processes that afford the development of teacher agency. A multiple case study design was adapted to examine how structures and processes within two lateral networks have assisted in developing teacher agency. The participants comprised teachers from schools and those from headquarter units. Analysis of the study reveals the affordances of the structures and processes of the networks that assist in empowering teachers to develop agency through connecting with other teachers. The findings illustrated the systematic organization of structures, processes, coordination, and activities of the networks that allowed teachers to try out new ideas collectively, concomitantly customizing to their individual needs. The contributions include three designs to characterize functioning of lateral networks in centralized systems, featuring co-constructions of structures and processes: (1) Negotiating between daily practices and networks activities to inform teaching; (2) Using innovations in converging teachers; (3) Organizing activities that are regular to create relations. To conclude, this study discusses a model of lateral networks towards teacher agency and its implications to management. The model offers centrality for the lateral networks in developing teacher agency. It capitalizes on the values of structures and processes for teachers to experiment with innovations which they would otherwise miss.